MISI PENDIDIKAN SPIRITUAL KENABIAN NABI MUHAMMAD (Analisis Ikhtiar Membentuk Karakter Anak Bangsa Dengan Pendekatan Hikmah) - Syarif Syarif (Khatulistiwa, 2011)
Education in the Islamic world, the real figure should appear Muhammad as the leading and most successful educators. But Muhammad did not appear today. Muhammad was especially touched by the mission in the practice of the educational process which is attributed to Islam except just touched in discourse without end. It happened because the essence of the mission of Muhammad is not understood. Missi Muhammad actually just about "morals". Today morals understood bias. Morals tend to be understood as a behavior (Af'al). Bias of understanding that was followed by a bias on the mode of delivery and source bias. Repair morals today leaning to "custodian" of learning. Though Muhammad said "I was raised to improve morals". It means that the process of moral improvement today one berthing. The Qur'an explains that "morals" as the subject and repairs must be returned to their home. Then steps should be taken before returning to his native morals, morality must recognize his form. By knowing his form, we will know the origin of morality. Then we would know it back to the source. Turned out Lord claimed that He alone can edify it. That is, any sophisticated educational process carried out by human beings will never be able to edify. Therefore, we must know how to restore moral behavior as subject to God. Based on this, this paper is written with “hikmah” approach.